Identifikasi Pemborosan Pada Proses Produksi Jamur Tiram Dengan Pendekatan Lean Manufacturing (Studi Kasus pada UMKM XYZ) - Rianti Indah Lestari; Nur Khaerani Busri (Jurnal Industri dan Teknologi Samawa, 2025)
XYZ MSMEs are oyster mushroom cultivation businesses by making Baglogs (planting media) which are used as mushroom growth media. The obstacle faced by XYZ MSMEs is that the demand is not met by an average of 70% caused by the non-achievement of mushroom production against the production target of 500 kg/month, this is due to a baglog defect of 40%. This research aims to identify non-value-added activities that can affect the production process. The method used in this study is using the Lean Manufacturing approach which includes three stages, namely Value Stream Mapping (VSM), Process Activity Mapping (PAM) and Fault Tree Analysis (FTA). The results of this study showed that there was a decrease in production process time of 252 minutes or 4 hours and 2 minutes from the total time before the repair of 58,592 minutes to 58,340 minutes. In addition, 5 (five) types of waste were also obtained, including waiting time, operation, transportation, motion and defect product. Based on the waste obtained, the factors that cause waste are identified using FTAs. Based on the results of the identification, improvement proposals were given, namely placing raw materials in the same place, providing work equipment (gas and plastic baglogs), supplying equipment racks, using material handling in the form of thrusters, increasing the number of operators and implementing SOPs in each baglog production process.